(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2023)
The text aims to analyze the relationship between artistic practice and urban space through the use of digital technologies (VR/AR, gaming) following the specific case of the city of Venice, immobilized between the process of over-touristification and that of emptying its residents, blocked between housing and climate emergency. The case studies here presented, therefore, want to analyze the relationship between artistic practice and the ecology of the city understood in the complex development of its social and environmental relationship in continuity with its lagoon. The case studies proposed are: Vacanze Intelligenti (Nico Angiuli); VR Pavilion (Sara Tirelli); Esperienza Pepe (Biennale Urbana); Metagoon (Matteo Stocco). Each of these, through its specific forms, demonstrates how virtuality can become the main way of designing a city that cannot over-build itself and therefore change its narrative.